Analysis of the use of the travelling rule in the European championship in basketball 2005 - Fosnaes, O.; Miller, B.; Knjaz, D. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
All ballgames have rules that define the way the game is supposed to be played. These so called primary or constitutive rules tells us how the players are allowed to act in order to try to score or bring the ball up the court, it also tells us how the players should act against each other. The most important rules concerning this are the travelling rule and the rules allowing or forbidding contact between the players. (Fosnæs 2009) Methods: 4 games of the European championship in Basketball in Serbia 2005 are analyzed. We are looking at every action in offense when a player receives the ball, starts a dribble, stops or make a shot. The actions are analyzed frame by frame on a screen. The actions are compared with the international rules of the game (FIBA rules). The registration will also tell what kinds of moves are made, and when there is a violation we will register the kind of mistake. Results: In average there are in general between 100 and 160 actions in every period. 1 or 2 of these actions are called as travelling violation according to the rule by the referee. In our analysis between 22 % and 40 % of the actions are violating the rules. Discussion: The referees do not have the same chance as we have to see the situation frame by frame, and watch it many times to study what kind of movement the players are doing. And some of these rule violations are almost impossible to observe without DVD. There are several concerns to discuss here. If a player gets an advantage violating the rule it is easy for the defensive player to be beaten or to make a foul in the next situation. The referees will always consider the situation, and call for the mistakes that are made. Sometimes it seems as if they have a common understanding of how they are to use the rule. As Fosnæs (2009) says the travelling rule and the contact rule are the most important rules describing how the game is to be played, a more loose way of calling the travelling rule might change the game. This again will influence on the teaching and learning of basketball both in schools and in the sport outside the schools. If the rule is difficult either to live up to or to call by the referees, may be the rule itself should be redefined? References: FIBA rules both 2005 and 2008 Referees manual DVDs from games in European championship in Serbia 2005 Ola Fosnæs 2009, The structural integrity of ballgames